2023
DOI: 10.2196/41092
|View full text |Cite
|
Sign up to set email alerts
|

Video-Based Educational Interventions for Patients With Chronic Illnesses: Systematic Review

Abstract: Background With rising time constraints, health care professionals increasingly depend on technology to provide health advice and teach patients how to manage chronic disease. The effectiveness of video-based tools in improving knowledge, health behaviors, disease severity, and health care use for patients with major chronic illnesses is not well understood. Objective The aim of this study was to assess the current literature regarding the efficacy of v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 103 publications
(468 reference statements)
0
3
0
Order By: Relevance
“…Health literacy-informed communication strategies have been included as part of interventions to improve understanding and implementation of instructions related to individual medications and chronic conditions. [38][39][40] Communication strategies (e.g., demonstration, showback) have been incorporated into interventions related to the management of equipment instructions for CMC. 13 Randomized trials evaluating objective outcomes of comprehension and adherence after incorporating such strategies into overall management of discharge instructions for CMC have not been studied and should be the focus of future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health literacy-informed communication strategies have been included as part of interventions to improve understanding and implementation of instructions related to individual medications and chronic conditions. [38][39][40] Communication strategies (e.g., demonstration, showback) have been incorporated into interventions related to the management of equipment instructions for CMC. 13 Randomized trials evaluating objective outcomes of comprehension and adherence after incorporating such strategies into overall management of discharge instructions for CMC have not been studied and should be the focus of future research.…”
Section: Discussionmentioning
confidence: 99%
“…While prior research has identified health literacy as a barrier to comprehension and adherence, 37 few studies have described pediatricians' perspectives on incorporating health literacy‐informed communication strategies into education for parents of CMC at discharge. Health literacy‐informed communication strategies have been included as part of interventions to improve understanding and implementation of instructions related to individual medications and chronic conditions 38–40 . Communication strategies (e.g., demonstration, showback) have been incorporated into interventions related to the management of equipment instructions for CMC 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, video based training programs showed effectiveness in many clinical contexts, such as improving patient’s knowledge in clinical settings and reducing anxiety and the sense of unfamiliarity that challenges the diagnostic procedures. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%